Arrythmic storm in patients with and without an implantable cardioverter defibrillator. (14th October 2021) - Garcia-Arribas, D; Fernandez Ramos, A; Viana, D R; Rosillo, S; Caro-Codon, J; Armada, E; Carrion, I; Ferrera, C; Noriega, F J; Lopez De Sa, E
Abstract: Introduction: Available data on arrhythmic storm (AS) is frequently obtained from retrospective observational series of patients who carry an implantable cardioverter defibrillator (ICD). Therefore, this selection bias limits the evidence regarding mortality and prognosis of patients with AS who do not have an ICD. Purpose: Describe and compare the epidemiological and clinical characteristics, treatment, and outcomes of patients with and without an ICD, admitted for AS in the Acute Coronary Care Unit. Methods: Between 2006 and 2020, 187 episodes of AS in 165 patients were identified in two third level hospitals. There were 71 patients without ICD and 116 patients with ICD. Clinical characteristics, treatment and outcome were analysed. Results: Baseline characteristics are depicted in Figure 1. Risk profile of ICD carriers was worse (they were older, more frequently smokers, had more often hypertension, dyslipidemia, chronic kidney disease and thyroid disturbances, and had worse NYHA class). Known ejection fraction was also worse. AS aetiology was also different. Myocardial infarction was present only in non ICD carriers (56.3% vs 0, p<0.001) and was the most frequent cause of AS in this group. Ion disturbances were also more common among ICD carriers (60.3% vs 33.6%, p<0.001), but it was the most frequent aetiology of AS in non ICD carriers. Heart failure or cardiogenic shock (36.6% vs 26.7%, p=0.154), infection (7% vs 13.8%, p=0.156) and bradycardia with acquired long QT syndrome (11.3% vs 9.5%, p=0.695) were similar in both groups. There were two episodes of myocarditis among non ICD carriers. The predominant arrythmia was also different. Ventricular fibrillation was more common in non ICD carriers (43.7% vs 4.3%) while monomorphic ventricular tachycardia was more frequent in ICD carriers (38.8% vs 83.6%, p<0.001). Non ICD carriers had worse levels of pH (7.30 vs 7.42, p<0.001) and lactate (4.4mmol/L vs 2.0mmol/L, p>0.001) and required inotropic and vasopressor drugs more frequently due to haemodynamic instability (57.7% vs 10.3%, p<0.001), mechanical support with intra-aortic balloon pump (40.8% vs 1.7%, p<0.001), ECMO (8.5% vs 0%, p<0.001), and other mechanical assist devices (5.6% vs 0%, p=0.010), and oral intubation (71.8% vs 17.2%, p<0.001). Pharmacologic treatment is described in Figure 2. Non ICD carriers required more frequently percutaneous coronary intervention (59.2% vs 4.3%, p<0.001) and less frequently ventricular ablation (28.2 vs 46.6%, p=0.013). Therapeutic hypothermia was used only in non ICD patients due to out of hospital cardiac arrest (33.8% vs 0%, p<0.001). In-hospital mortality was higher in non ICD carriers (28.2% vs 11.2%, p=0.003). Conclusion: Despite a worse cardiovascular profile in ICD carriers, AS is associated with a worse haemodynamic situation and mortality in non ICD carriers, due to different aetiology of the AS and to the absence of protection against sustained arrythmias. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Beca para la Formaciόn e Investigaciόn en Cuidados Críticos Cardiolόgicos concedida por la Asociaciόn de Cardiopatía Isquémica y Cuidados Críticos Cardiolόgicosde la SEC